The Symbol of Door as Mary in Images of the Annunciation of the 14th-15th Centuries (Fenestella. Inside Medieval Art, 2021)
The current article addresses the topic of the symbolic identification of the Virgin Mary as a door according to a double possibility, namely, as an open door and as a shut door. This implies designating Mary simultaneously as ianua coeli and as porta clausa. These two possibilities suggest very different, though complementary, doctrinal meanings. Through the textual analysis of various quotes from the Church Fathers and theologians and medieval liturgical hymns referring to one or other of these two metaphorical expressions, the Author will determine the doctrinal meanings inherent in each one.In the second instance, the iconographic analysis of seven images of the Annunciation from the 14th and 15th centuries that include some door in special conditions will allow us to validate the hypothesis that the intellectual authors of these seven paintings introduced that door into them as a visual metaphor capable of illustrating both textual metaphors of porta clausa and ianua coeli.
Keywords: Virgin Mary; Divine motherhood; Virginity; Corredemption; Patristics; Annunciation; Iconography; Porta clausa; ianua coeli